Analysis Of Factors Related To Workload Of Nurses At UPT Rumbia Regional Public Hospital Jeneponto District - Nurbaya, Nurbaya; Zainuddin, Zainuddin; Muhammad Basir (Jurnal EduHealth, 2024)
Nurse workload is the average frequency of each type of work in a certain period of time that must be carried out by health workers. This workload must receive attention because it is one of the bases in preparing a health worker needs plan. Excessive workload will affect the productivity of health workers, while the workload is caused by the number of health workers that is not yet adequate. This study aims to analyze factors related to the workload of nurses at the UPT Rumbia Regional General Hospital, Jeneponto Regency. Type of research used The type of research conducted is an analytical observational study with a cross-sectional study design. Collecting data through questionnaires. In this study, 72 nurses working at the UPT Rumbia Regional General Hospital, Jeneponto Regency were the subjects. Data analysis using the chi-square test.  The results of the study showed that the workload of nurses at the UPT Rumbia Regional General Hospital, Jeneponto Regency was related to job descriptions (p = 0.006), facilities/means (p = 0.019), additional tasks (p = 0.000), and the number of examinations (p = 0.010). The workload on all variables studied in this study showed that there was a relationship between the workload of nursing staff. It is expected that nurses at the UPT Rumbia Regional General Hospital, Jeneponto Regency who have less workload will develop their work and need to improve their skills.